Source code plagiarism detection approaches: a systematic literature review - Manahi, Mohammed; Sulaiman, Suriani; Awang Abu Bakar, Normi Sham; Nordin, Azlin; Ismail, Amelia Ritahani; Hassan, Raini (Institute of Advanced Scientific Research, 2020)
Source code plagiarism is a widespread concern in academia as a consequence of students do commit this malpractice in programming assignments for an academic credit. Programming instructors carry out human inspection to expose plagiarized source codes. However, such manual inspection embodies laborious duty to accomplish adequate assessment to preserve academic integrity. Therefore, various researchers and practitioners in this field proposed approaches to detect suspicious source codes which comprise potential plagiarism activities. This research paper discusses source code plagiarism phenomenon amongst students in programming classes. More significantly, it conducts a systematic literature review of diverse detection approaches for source code plagiarism and their methodological classifications. The systematic literature in this work reviews forty studies of thirty-nine detection approaches that comprise of thirty-five detection approaches proposed in published research papers and four approaches sought out in theses.